2022
DOI: 10.3390/horticulturae8030237
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Phytopharmaceutical and Alkaloid Production in Periwinkle Plants by Endophyte and Abiotic Elicitors

Abstract: Periwinkle plant represents a major source of immensely vital terpenoid indole alkaloids and natural antioxidants which are widely used in cancer chemotherapy. A pot experiment was done to evaluate the role of two periwinkle endophytes (Streptomyces sp. and Bacillus sp.) with or without abiotic elicitors (aluminum chloride, tryptophan, and chitosan) on plant biomass, physio-biochemical attributes, phytopharmaceutical constituents, and alkaloid production. Inoculation with endophyte microbes significantly incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 73 publications
1
2
0
Order By: Relevance
“…In this study, application BS agents resulted in a decrease in the synthesis of flavonoids, as well as an increase in the synthesis of DNJ in mulberry leaves. This is consistent with previous studies showing that inoculation with PGPR has the potential to increase alkaloid yield in plants [35,36] but inconsistent with the results stating that B. subtilis-treated plants exhibited significantly improved synthesis of flavonoids [26,37,38].…”
Section: Impact Of Bs On Flavonoids and Alkaloids Accumulationsupporting
confidence: 74%
“…In this study, application BS agents resulted in a decrease in the synthesis of flavonoids, as well as an increase in the synthesis of DNJ in mulberry leaves. This is consistent with previous studies showing that inoculation with PGPR has the potential to increase alkaloid yield in plants [35,36] but inconsistent with the results stating that B. subtilis-treated plants exhibited significantly improved synthesis of flavonoids [26,37,38].…”
Section: Impact Of Bs On Flavonoids and Alkaloids Accumulationsupporting
confidence: 74%
“…It is widely reported that endophyte-mediated plant growth improvement occurs through biofertilization and biostimulation: (i) providing the hosts with water and essential nutrients, such as N and P, by transforming them into effortless types, being digestible (using N fixatives, P solubilizers, siderophore producers, etc.) [19][20][21]91]; (ii) the synthesis of growth phytohormones (auxins (IAA), cytokinins (CKs), and gibberellins (GBs)) or alter the synthesis of stress and signaling phytohormones (i.e., abscisic acid (ABA), salicylic acid (SA), ethylene, and jasmonates) [19,21,23,[92][93][94]; and (iii) the synthesis of many compounds with protective and signaling functions (i.e., antibiotics, enzymes, siderophores, LPs, hydrogen cyanide and others) [30,31,82,90,94,95] (Figure 2). Endophytes are capable of dissolving water-insoluble and other inaccessible forms of P, K, Mg and other essential compounds through the production of organic and inorganic acids, protons, hydroxyl ions and CO2 that facilitate their uptake by plants [96][97][98][99][100].…”
Section: Microbial Endophytes-mediated Biofertilization and Biostimul...mentioning
confidence: 99%
“…Nowadays, the ubiquity of endophytic microorganisms is widely recognized and the opportunities for their use in crop production are of great interest [14][15][16][17]. The physiological action of beneficial microbial endophytes on host plants is associated with effective competition for space and nutrients with phytopathogens [18], improving the bioavailability of macro-/microelements and the mineral nutrition of plants [19][20][21], photosynthesis [22,23], stomatal conductance [24], water status [25], modulating the endogenous hormonal background influencing the architecture of the root system [26,27], regulating the production of phytohormones and their accumulation in plants [14,26,27], activating the synthesis of various antioxidant and osmoprotective compounds [28,29], various biologically active substances [19,[29][30][31] and signaling molecules that activate induced systemic defense in hosts against biotic [32][33][34] and abiotic stresses [35,36]; thereby leading to better plant growth, yield and product quality.…”
Section: Introductionmentioning
confidence: 99%